Microstructure of fibrils separated from polyacrylonitrile fibers by ultrasonic etching - Wang, QiFen; Wang, ChengGuo; Yu, MeiJie; Ma, Jie; Hu, XiuYing; Zhu, Bo (Science China Technological Sciences, 2010)
Polyacrylonitrile (PAN) fiber is an important precursor fiber for high performance carbon fiber. The properties of the final carbon fiber depend strongly on the nature of the PAN fibers. The PAN fibrils were separated successfully from fibers by ultrasonic etching and were systematically investigated by field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM). It is found that in certain ultrasonic etching conditions (at 75±2°C for 6 h with a frequency of 40 kHz) the PAN fibers are dissolved in the 95 wt.% aqueous dimethylsulphoxide (DMSO) solution; the fibrils consisting of numerous periodic lamellae with thickness of 30–45 nm and perpendicular to the fiber axis are separated in the 90 wt.% aqueous DMSO solution; and the fibrils with smooth surface exfoliated from the PAN fibers are obtained in the 70–90 wt.% aqueous DMSO solutions. Inner periodical structure of fibrils was observed in HRTEM, which indicates that there are different densities and two phases in fibrils. The PAN fibers are dissolved layer by layer with increasing ultrasonic etching time. The fiber surface experiences ultrasonic cleaning, selective etching, excessive etching and dissolution, and then the sublayer experiences the same process. There are numerous periodic lamellae in fibrils of nascent fibers. This means that the fibrils with lamellae are formed by orientation and crystallization in shearing field of spinning pipe and drawing stress field of coagulation bath.